Perception of old shop houses owners and community attachment towards the conservation of old shop houses in Muar town, Johor. - Fazil, Nur Dalili Faqihah; Saad, Mazni (2020)
Heritage conservation has been a must achievement for every country. The concept of conservation is more than the architectural elements. People and community within the heritage area plays role in the conservation of heritage buildings. In Muar, although the region, it’s not listed in UNESCO World Heritage Sites, there are various types of heritage buildings that can be seen clearly. Few old shop houses are changed not only its façade but the building structure, style and design that has been overshadowed by modern construction materials. Therefore, it is important to identify the level of awareness of old shop houses owners and the community to conserve the buildings in Muar town. The research method used qualitative research. The respondents in this study were the owners of the old shop houses and the community that lives in Muar. The research data were collected using a semi-structured interview via telephone. The results of this study indicate the level of awareness among old shop house owners and Muar community from their perceptions and attachments towards the buildings itself. The significance of this study shown to measure the level of awareness of Muar community to conserve old shop houses and their understanding about the building’s conservation, which further can be used by Muar authorized conservation practice, conservationist and expertise to ensure the conservation goals in Muar can be achieved.